2017
DOI: 10.1177/1744806917724259
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphism in the COL11A2 gene associated with lowered heat pain sensitivity in knee osteoarthritis

Abstract: Pain is one of the most prominent symptoms of osteoarthritis. However, there is often discordance between the pain experienced by individuals with osteoarthritis and the degree of articular pathology. This suggests that individual differences, including genetic variability in the central processing of nociceptive stimuli, may impact the presentation of osteoarthritis. Here, we show that the single nucleotide polymorphism rs16868943 in the collagen gene COL11A2 is significantly associated with lowered heat pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…It is possible that variants in the COL27A1 gene could eventually affect the quality of the tendons such as strength or flexibility, which might lead to poor tendon function, or their stability of the attachment to the patella, which might also be knee pain related. A recent study has suggested that a collagen gene COL11A2 play a role in pain sensitisation after the development of osteoarthritis 43 . Interestingly, the COL27A1 gene was not mentioned in GWAS on osteoarthritis using the UK Biobank dataset 44 .…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that variants in the COL27A1 gene could eventually affect the quality of the tendons such as strength or flexibility, which might lead to poor tendon function, or their stability of the attachment to the patella, which might also be knee pain related. A recent study has suggested that a collagen gene COL11A2 play a role in pain sensitisation after the development of osteoarthritis 43 . Interestingly, the COL27A1 gene was not mentioned in GWAS on osteoarthritis using the UK Biobank dataset 44 .…”
Section: Discussionmentioning
confidence: 99%
“…COL11A2 is a member of the fibrillar collagen subgroup, which encodes α chains of type XI collagen 11. It has been reported that COL11A2 may associate with pain sensitivity in OA 12…”
Section: Introductionmentioning
confidence: 99%
“…Genetic factors are known to impact pain perception and formation. Common genetic polymorphisms have been shown to affect the development and perception of pain [20, 21]. Rare, single-gene variants causing painful phenotype are less common [2224].…”
Section: Discussionmentioning
confidence: 99%